Resiliensi Perilaku Self Harm Pada Remaja Wanita: Penelitian - Marssel Michael Sengkey; Nova Lisye Sinaulan; Angraini Tri Ivana. T; Vrisilia Pandaleke; Pratika Dwifarsi Durian (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to understand resilience in adolescent girls with a history of self-harm. Using a phenomenological approach, six participants aged 14–18 were interviewed in depth. Self-harm was found to be a response to emotional stress, family conflict, academic pressure, and feelings of loneliness. Despite this, participants showed resilience through positive coping, social support, self-reflection, creative expression, and self-compassion. Resilience emerged as a process shaped by crisis experiences and meaning-making. The study highlights the importance of psychological approaches that consider individuality and personal strengths in preventing and recovering from self-harm.